Hydrogen and oxygen isotopes in vertebrate tissues vary by diet type - Reynard, Linda M.; Leichliter, Jennifer N.; Winkler, Daniela E.; Clauss, Marcus; Tütken, Thomas (Frontiers in Ecology and Evolution, 2025)
Hydrogen and oxygen isotope ratios in proteinaceous tissues have been used for some time in migratory, ecological, and archaeological studies. While the result of isotopic variation in drinking water and diet has been investigated with controlled feeding experiments and studies in the wild, there are few controlled feeding studies that manipulate the diet components and diet type, and this across different taxa. In this experiment, the diet fed to rats, guinea pigs, and quail varied from plant-based to insect-based and meat-based pelleted diets. We report the diet to tissue offsets for δ2H (denoted Δδ2H) and δ18O (Δδ18O) of tissue-bound organic matter in two tissue types: muscle and dentine collagen. The diet to tissue offset varies by diet type in muscle of all three species, by up to 16 ‰ (Δδ2H) and 2 ‰ (Δδ18O). In dentine collagen, a range of ~20 ‰ in Δδ2H and ~1.5 ‰ in Δδ18O are observed across diets, though in a smaller number of samples. Additionally, we note large variation in Δδ2H and Δδ18O by tissue type (δ2H = ~60 ‰, δ18O = ~3–4 ‰) and more moderate differences by species (up to δ2H = 7.4 ‰, δ18O = 1.5 ‰). The difference in consumer tissue Δδ2H and Δδ18O by diet type is important to consider as a source of isotopic variability for some studies such as migratory research or diet or drinking water reconstructions and (palaeo-)climate inferences drawn from them, particularly in species that may vary their dietary habits.